Meningkatkan Kemampuan Membaca Permulaan Anak Usia Dini Melalui Permainan Memancing Huruf Pada Kelompok A TK Aisyiyah 3 Bustanul Athfal Sepat Masaran SragenTahun Pelajaran 2015/2016 - Murni, Tri, Drs. Ilham Sunaryo, M.Pd. AUD (2016)
Background problem in this research is the lack of ability to recognize letters A group of children in kindergarten Aisyiyah 3 Bustanul Athfal Sepat Masaran Sragen and teachers do not use the media effectively and efficiently in learning recognize letters. The purpose of this study was to determine the increase in children's ability to read the beginning of the group A kindergarten Aisyiyah 3 Bustanul Athfal Sepat Masaran Sragen Academic Year 2015/2016. This research is a classroom action research, conducted in two cycles each cycle consisting of two meetings. The technique of collecting data through observation, interviews and documentation. Based on the results of research can be concluded that there is an increased ability to read the beginning of kindergarten children Aisyiyah 3 Bustanul athfal Sepat Masaran Sragen. Academic Year 2015/2016 of prasiklus obtain a percentage of 30%, one cycle of 33% the first meeting, one cycle of 48% the second meeting, the first meeting of the second cycle and the second cycle 61% 82% the second meeting. The conclusion that through the fishing game on kindergarten letter Aisyiyah 3 Bustanul Atfal Sepat Masaran Sragen can be increased as expected. In the second cycle which gets a percentage of 82% while 80% of the specified targets.